Pleistocene Ice Ages Created New Evolutionary Lineages, but Limited Speciation in Northeast Pacific Winged Kelp. (30th November 2020) - Grant, W Stewart; Bringloe, Trevor T
Abstract: The extent that Pleistocene climate variability promoted speciation has been much debated. Here, we surveyed genetic markers in winged kelp Alaria in the Gulf of Alaska, Northeast Pacific Ocean to understand how paleoclimates may have influenced diversity in this kelp. The study included wide geographic sampling over 2800 km and large sample sizes compared to previous studies of this kelp. Mitochondrial 5′- COI (664 bp), plastid rbc L-3′ (740 bp) and 8 microsatellite markers in 16 populations resolved 5 well-defined lineages. COI - rbc L haplotypes were distributed chaotically among populations around the Gulf of Alaska. Principal Coordinates Analysis of microsatellite genotypes grouped plants largely by organellar lineage instead of geography, indicating reproductive isolation among lineages. However, microsatellite markers detected hybrids at 3 sites where lineages co-occurred. Local adaptation on various time scales may be responsible for some genetic differences between populations located along wave-energy and salinity gradients, but the chaotic pattern of variability over hundreds of kilometers is likely due to isolations in northern refugia during Pleistocene ice ages. The range of divergences between populations indicates that episodic glaciations led to the creation of new lineages, but population turnover (local extinctions and recolonizations) limited the formation of new species in the Northeastern Pacific Ocean. Graphical Abstract: